Fucoxanthin Inhibits the NMDA and AMPA Receptors Through Regulating the Calcium Response on Substantia Gelatinosa Neurons of the Trigeminal Subnucleus Caudalis in Juvenile Mice - Nhung Ha Thuy Le; Seon Ah Park; Yu Mi Kim; Dong Kuk Ahn; Won Jung; Seong Kyu Han (Neural Plasticity, 2025)
Glutamate excitotoxicity is considered as the etiology of stroke and neurodegenerative diseases, namely, Parkinson’s disease (PD), Alzheimer’s disease (AD), and others. Meanwhile, substantia gelatinosa (SG) neurons of the trigeminal subnucleus caudalis (Vc), a pivotal site in regulating orofacial nociceptive transmission via Aδ and C primary afferent fibers, majorly utilize glutamate as the principal excitatory neurotransmitter. Fucoxanthin (FCX), a carotenoid pigment extracted from brown seaweed, possesses various pharmaceutical properties including neuroprotective effect in multiple neuronal populations. To date, the direct activity of FCX on the SG of the Vc has not been extensively clarified. Consequently, we investigated the effect of FCX on excitatory signaling mediated by ionotropic glutamate receptors (iGluRs), using the patch-clamp technique recorded from SG neurons of the Vc. Here, FCX directly acted on glutamate receptors independent of voltage-gated sodium channel and γ-aminobutyric acid (GABA)A/glycine receptors in the voltage-clamp mode. Specifically, the N-methyl-D-aspartic acid (NMDA)- and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-induced responses but not the kainic acid receptor (KAR)-mediated response were suppressed by FCX in standard extracellular solution. Additionally, the inhibitory effect of FCX on NMDA currents was repeatable and concentration-dependent. The FCX blockade of NMDA-mediated excitotoxicity was associated with the modulation of Ca2+ response without affecting Na+ ions. The Ca2+-dependent fluorescence intensity of brain slice was reduced in the presence of FCX. Notably, FCX significantly attenuated the spontaneous firing activity of SG neurons. Altogether, these results reveal that FCX may protect SG neurons against glutamate excitotoxicity via primarily regulating Ca2+ response, thereby inhibiting the excitatory signaling induced by NMDA and AMPA receptors (AMPARs).